Combating global warming : possible rules,regulations and administrative arrangements for a global market - United Nations Conference on Trade and Development (New York : United Nations, 1994)
The book explores the strategies of combating global warming thereby explaining some possible rules, regulations and administrative arrangement.
At head of title: United Nations Conference on Trade and Development.
"UNCTAD/RDP/DFP/1."
Includes bibliographical references.
ii 14/01/2019
Loans
Keywords: Global warming; Carbon dioxide; Environmental policy